Asymmetric volatility effects in risk management: An empirical analysis using a stock index futures - Guillermo Benavides (Banco de México, 2020)
In this research paper ARCH-type models and option implied volatilities (IV) are applied in order to estimate the Value-at-Risk (VaR) of a stock index futures portfolio for several time horizons. The relevance of the asymmetries in the estimated volatility estimation is considered. The empirical analysis is performed on futures contracts of both the Standard and Poors 500 Index and the Mexican Stock Exchange. According to the results, the IV model is superior in terms of precision compared to the ARCH-type models. Under both methodologies there are relevant statistical gains when asymmetries are included. The referred gains range from 4 to around 150 basis points of minimum capital risk requirements. This research documents the importance of taking asymmetric effects (leverage effects) into account in volatility forecasts when it comes to risk management analysis.
Keywords: C15; C22; C53; E31; E37; 330; Asymmetric volatility; Backtesting; GARCH; TARCH; Implied volatility; Stock indexfutures; Value at Risk; Mexico